SEA LEVEL AND PALAEOCLIMATIC CHANGES IN THE SOUTH AND MIDDLE CASPIAN SEA REGION SINCE THE LATEGLACIAL FROM PALYNOLOGICAL ANALYSES OF MARINE SEDIMENT CORES - Suzanne Leroy (Geography, Environment, Sustainability, 2010)
A review of pollen, spores, non-pollen palynomorphs and dinocyst analyses made in the last two decades is proposed here. Building on spare palynological analyses before 1990, a series of new projects have allowed taking cores in the deeper parts of the Caspian Sea, hence providing access to low-stand sediment. However, still nowadays no complete record exists for the Holocene. The first steps towards quantification of the palynological spectra have been taken. Some of the most urgent problems to solve are the uncertainties related to radiocarbon dating, which are especially acute in the Caspian Sea.